Synthesis of multinational marine aquaculture and clean energy co-location - Gonzales, Claire M.; Chen, Samantha; Froehlich, Halley E. (Frontiers in Aquaculture, 2024)
Marine co-location, i.e., multiple fixed ocean activities operating in the same place and at the same time, can maximize the space- and resource-use efficiency in crowded seascapes. While interest grows, commercial use is nascent and the collective benefits or limitations of co-locating aquatic food and clean energy remains scattered throughout the literature. In this study, we synthesize multinational findings of co-location scientific publications (N = 102) to better understand the patterns and knowledge gaps at the co-located ocean food-energy nexus. We track and compare food (aquaculture) and energy (tidal, offshore wind, and wave) co-located ocean activities, noting the focus (e.g., ecological), motivation (e.g., impact/risk), and assessment type (e.g., modeling), as well as nine key metrics of interest (depth, distance from shore, aquaculture yield, etc.), mainly for aquaculture co-location. We found the number of annual co-location publications increased over time and space but are largely concentrated in the North Sea (n = 39). We also found about half of publications include aquaculture, one-third of publications report at least one metric – reporting aquaculture yield was particularly rare (n = 1) – and few studies focused on impact/risk (n = 7). However, conducting a targeted post-hoc evaluation of North Sea gray literature (N = 61), due to this region’s importance in the field, showed more coverage of impacts/risk (e.g., liability) and similar attention to aquaculture. Of the scientific papers that did report metrics, the ranges of depth and distance exceeded those reported for standalone sectors, indicating co-location could be facilitating a “push” of ocean activities into farther offshore and/or deeper exposed waters. Ultimately, while aquaculture is commonly cited in the co-location literature, the shortage of metrics, like aquaculture yield, and possible impact/risk evaluations – though gray literature can provide critical insights – emphasizes the need for knowledge sharing and modeling to address and explore the uncertainty, especially for co-located aquaculture production. This study provides a needed snapshot of marine co-location, particularly in emerging regions, highlighting gaps in understanding aquaculture-energy potential in the oceans.